Hubungan Perilaku Anak Sekolah Dasar dengan Kejadian Schistosomiasis di Kecamatan Lindu Kabupaten Sigi, Sulawesi Tengah - Octaviani Octaviani; Phetisya Pamela Frederika Sumolang; Murni Murni; Nelfita Nelfita (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2017)
Schistosomiasis is a parasitic disease caused by infection of Schistosoma japonicum, S. haematobium, S. mansoni, S. mekongi, and S. intercalatum. It is transmitted to definitive host through cercaria contaminated water. In Indonesia, schistosomiasis was caused by S. japonicum which can be found in endemic areas at Lindu, Napu, and Bada highland. Schistosomiasis can infect all people regardless their age. If untreated, it leads to a chronic condition. Children who are infected will have a growth and cognitive problem and even death. The transmission of schistosomiasis cannot be separated from people behavior. This study aimed to identify the relationship between behavior of elementary student and schistosomiasis settle in Lindu, Sigi District, Central Sulawesi for eight months from March to December 2014. This was an observational study with a cross-sectional design. The data were collected by stool sampling and interview on elementary students. Stool samples were examined by Kato-Katz method. The chi-square analysis showed that there was no relationship between bathing habits, defecation habits, and using boots to schistosomiasis.